Study of Anti-Corrosion Properties of Sodium Dodecyl Sulphate and Cetyl Pyridinium Chloride - Yadav, Chandradip Kumar; Niraula, Tulasi Prasad; Neupane, Shova; Yadav, Amar Prasad; Bhattarai, Ajaya (Journal of Nepal Chemical Society, 2024)
Surfactant is a surface-active agent. Surfactants have both hydrophilic (water-attracting) and hydrophobic (water-repelling) portions in their molecular structure, effective inhibitors for the protection of mild steel in an acidic medium, the weight loss methods were used at lab temperature to evaluate the effect of surfactant cetyl pyridinium chloride (CPC) and sodium dodecyl sulfate (SDS) on the corrosion protection behavior of Mild steel in 0.5 M H2SO4 solution. Inhibition efficiency, weight loss, corrosion rate, and surface coverage area of Mild steel in different concentrations of surfactant were studied. The results showed that the Inhibition efficiency of cetyl pyridinium chloride is 99.86%, which is greater than that of sodium dodecyl sulfate (99.85%) in the presence of 0.5 M H2SO4.